Understanding the role of threading dislocations on 4H-SiC MOSFET breakdown under high temperature reverse bias stress. (8th January 2020) - Fiorenza, P; Alessandrino, M S; Carbone, B; Di Martino, C; Russo, A; Saggio, M; Venuto, C; Zanetti, E; Giannazzo, F; Roccaforte, F
Abstract: The origin of dielectric breakdown was studied on 4H-SiC MOSFETs that failed after three months of high temperature reverse bias stress. A local inspection of the failed devices demonstrated the presence of a threading dislocation (TD) at the breakdown location. The nanoscale origin of the dielectric breakdown was highlighted with advanced high-spatial-resolution scanning probe microscopy (SPM) techniques. In particular, SPM revealed the conductive nature of the TD and a local increase of the minority carrier concentration close to the defect. Numerical simulations estimated a hole concentration 13 orders of magnitude larger than in the ideal 4H-SiC crystal. The hole injection in specific regions of the device explained the failure of the gate oxide under stress. In this way, the key role of the TD in the dielectric breakdown of 4H-SiC MOSFET was unambiguously demonstrated.